Enhancing Financial Sustainability and Commercial Viability of Bus Rapid Transits in Sub Saharan Africa : The Factor Analysis Report - Fan, Hongye; Beukes, Edward Andrew (World Bank, Washington, DC, 2021)
Rapid urbanization and urban population growth are placing increasing pressure on the transport systems of Sub Saharan Africa (SSA) cities. In response, major cities in the region have implemented or are in the process of implementing bus rapid transit (BRT) systems, which is seen as an affordable way to address the mobility challenges. To enable a financially sustainable BRT system and mobilize private capital more efficiently, it is critical for SSA governments to have an in-depth understanding and comprehensive assessment of these factors to develop contextually appropriate, effective solutions. This study aims to assist both public and private sector stakeholders to enhance the financial sustainability and commercial viability of BRT systems in SSA by: (i) identifying, framing, and analyzing the key factors influencing the financial sustainability and commercial viability of SSA BRTs; and (ii) developing a robust analytical tool to guide a high-level assessment of the factors influencing the financial sustainability and commercial viability of SSA BRT systems. The study was conducted in five stages: (1) project inception, (2) desktop review, (3) stakeholder engagement, (4) factor identification and analysis, and (5) assessment tool development. Chapter one introduces the objectives and context of the project. Chapters two and three capture key findings for several major BRT initiatives, in particular in Cape Town (South Africa), George (South Africa), and Dar es Salaam (Tanzania), providing a basis for the characterization of challenges and factors that impact financial sustainability and commercial viability. Chapter four articulates nine fundamental factors and their associated key actions and recommendations to enhance BRTs’ financial sustainability and commercial viability. Finally, chapter five provides a user guide for the factor assessment tool that should be used by decision makers when exploring the possibility of developing BRTs as an urban mobility solution.